2013
DOI: 10.1111/jan.12270
|View full text |Cite
|
Sign up to set email alerts
|

The case for nurses as central providers of health and social care services for ex‐offenders: a discussion paper

Abstract: The use of nurses in the provision of health and social care interventions to ex-offenders is a strategy, which could increase equity in access to health care, reduce reoffending and improve both the health and life chances of these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The Silences Framework has been used in a range of empirical studies, which centralize previously hidden or marginalized aspects of human experience in specific contexts that are deemed "sensitive." These have included studies of experiences of health provision for newly released offenders (Eshareturi et al, 2015;Eshareturi et al, 2014), exploration of HIV stigma within Black Sub-Saharan African communities residing in the UK (Nyashanu and Serrant, 2016), living with comorbidities of HIV and Tuberculosis in Brazil (Rossetto et al, 2018) and the recovery experiences of young adults following proximal fracture of the femur following a low velocity fall (Janes et al, 2018) with further studies currently underway.…”
Section: The Silences Framework (Overview)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Silences Framework has been used in a range of empirical studies, which centralize previously hidden or marginalized aspects of human experience in specific contexts that are deemed "sensitive." These have included studies of experiences of health provision for newly released offenders (Eshareturi et al, 2015;Eshareturi et al, 2014), exploration of HIV stigma within Black Sub-Saharan African communities residing in the UK (Nyashanu and Serrant, 2016), living with comorbidities of HIV and Tuberculosis in Brazil (Rossetto et al, 2018) and the recovery experiences of young adults following proximal fracture of the femur following a low velocity fall (Janes et al, 2018) with further studies currently underway.…”
Section: The Silences Framework (Overview)mentioning
confidence: 99%
“…Through the exploration of the intersectional nature of Black Women's sexual and reproductive health in the UK as an example, I present here an emerging framework for conducting health research on culturally sensitive health issues, The Silences Framework (Serrant-Green, 2011) to address this need. The Silences Framework has been successfully used elsewhere for conducting research on sensitive issues from the perspective of individuals and groups whose lived experiences of health and well-being have previously remained "silenced" (Eshareturi et al, 2014(Eshareturi et al, , 2015Nyashanu and Serrant, 2016;Janes et al, 2018). In this paper I will explore how the framework, may be aligned with, and drawing on aspects of existing intersectional theory and frameworks, can be used by researchers to expose the intersectional nature of issues which influence and may inform individual and group understandings of health, well-being and life chances for Black women in the UK diaspora.…”
Section: Introductionmentioning
confidence: 99%
“…They were people who lived in conditions of extreme vulnerability, and who were often liable and blamed for being in these conditions. Studies (10)(11) with persons serving a sentence in the prison system have shown that these research participants are often stigmatized by health professionals and that former offenders could be better cared for if the services could understand their health and structural needs better.…”
Section: It Took Time In the Health Center To Know What It Was (P7)mentioning
confidence: 99%
“…Offenders on release in England and Wales use health services in a crisis led way, are socially excluded and hard to reach (Rennie, Senior & Shaw, 2009;Norman, 2010;NHS Commissioning Board, 2013;Byng, Quinn & Sheaff, 2014). Whilst health services in prison is freely available, connecting released offenders with community health services as a health excluded group in need of tailored support is not prioritized (Van den Bergh, Gatherer, Fraserb & Mollera, 2011;Eshareturi, Serrant-Green & Bayliss-Pratt, 2014). In response to this, the aim of this study was to map the released offender health pathway towards identifying 'touch points' in the community where nurse led interventions could be delivered.…”
Section: Introductionmentioning
confidence: 99%